Behavioral efficiency I: Definition, methodology and demonstration - Ronald M. Harstad (Osaka University, Institute of Social and Economic Research (ISER), 2011)
Economic experiments conducted in laboratories employing an induced-values methodology can report on allocative efficiencies observed. This methodology is limited by requiring the experimenter to know subjects' motivations, an impossibility in field experiments. Allocative efficiency implies a hypothetical costless aftermarket would be inactive. An outcome of an allocation mechanism is herein defined to be behaviorally efficient if an appropriate aftermarket is actually appended to the allocation mechanism and at most a negligible aggregate size of mutually beneficial gains is observed on the aftermarket. Methodological requirements for observation of behavioral efficiency or inefficiency are put forward. A simple field demonstration indicates when an increase in public good output can cover marginal cost in a mutually beneficial decentralization, without knowing valuations. Several empirical issues that arise with the methodology are noted.
Keywords: C9; C93; D01; D61; D03; D46; 330; behavioral efficiency; field experiment methodology; allocative efficiency; revelation of valuations; aftermarkets; Marktmechanismus; Allokationseffizienz; Verhaltensökonomik; Auktionstheorie